Effect of Sugarcane Bagasse and Rice Husk Biochar for Remediating Heavy Metal Contaminated Soils and Enhancing Agro-Ecological Productivity - Huma, Noor; Khan, Nasir Mehmood; Yasin, Ahsan; Khan, Muhammad Amaid; Mujtaba, Ghulam; Naz, Saeeda; Nawaz, Shahid; Ali, Mehar; Zafar, Ibtesam (Indus Journal of Bioscience Research, 2025)
Heavy metal contamination of agricultural and industrial soils is becoming an issue of great concern for scientists and environmentalists. In recent years, biochar has emerged as an efficient and cost-effective tool for adsorption of heavy metals and reducing their availability to crop plants. Soil contaminated with cadmium and lead was treated with sugarcane bagasse and rice husk biochar at varying rates (0.5–2%). Effects on metal adsorption, soil properties, and nutrient availability were evaluated through incubation and pot experiments. Biochar application reduced cadmium and lead availability, with sugarcane bagasse biochar being more effective than rice husk biochar. At a 2% application rate, cadmium and lead concentrations decreased by over 60% compared to untreated soil. Soil pH increased significantly, supporting reduced metal mobility and improved soil health. Total organic carbon and nutrient availability, including nitrate, phosphorus, and potassium, were maximized at higher biochar rates. The results highlight sugarcane bagasse biochar’s superior performance in remediating heavy metal-contaminated soils and enhancing agro-ecological productivity. This study demonstrates that sugarcane bagasse biochar effectively reduces heavy metal availability in soil while enhancing soil fertility and crop growth. Biochar at 2% is a sustainable solution for reclaiming polluted soils and improving agro-ecological productivity.